Arctic Environmental Test of Fixed Wing Aircraft. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The Environmental Test Procedure describes test methods and techniques for evaluating the performance and characteristics of Fixed Wing Aircraft under Arctic winter conditions. Evaluation is related to criteria established by Qualitative Materiel Requirements (QMR)4 Small Development Requirements (SDR), Technical Characteristics (TC), or other applicable design requirements or specifications. Where criteria is limited in scope or lacking, comparison testing with a similar type aircraft in the inventory may be necessary. (Author)